PEM electrolyzed water membrane electrode based on modified Nafion ionomer and preparation method of PEM electrolyzed water membrane electrode
By doping the Nafion ionomer, introducing CF3(CF2)nCH2OH small molecules to form modified Nafion ionomers, the problem of poor stability of the catalyst under acidic conditions is solved, and the stability of the catalyst and the overall performance of the PEM electrolytic system are significantly improved.
Patent Information
- Application Number
- CN202411888473.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
In the existing PEM electrolytic system, it is difficult for the catalyst to maintain stability under acidic conditions, which limits the selection of catalysts and the stability of the system.
By doping commercial Nafion ionomers, CF3(CF2)nCH2OH small molecules are introduced to form modified Nafion ionomers (FOHn-Nafion) to optimize water channels and hydrogen bonded water networks and enhance the stability of the catalyst.
Modified Nafion ionomers significantly improve the stability of the catalyst. Especially under high current density conditions, the stability of the tricobalt tetroxide catalyst is increased by 10 times, the voltage is reduced, and the system performance is optimized.
Smart Images

Figure CN119798892A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy materials, and in particular relates to a PEM water electrolysis membrane electrode and a preparation method thereof. Background Art
[0002] As an efficient and environmentally friendly method of hydrogen production, water electrolysis technology has the potential to dominate the hydrogen production market in the future. This technology converts intermittent energy such as solar energy and wind energy into storable hydrogen resources. When needed, it can achieve on-demand power supply through the flexible application of fuel cell technology, ensuring zero carbon emissions in the entire process, demonstrating its significant advantages in the field of energy conversion and storage.
[0003] To further improve the efficiency of hydrogen production by water electrolysis, researchers are developing new electrolyzers and catalysts. For example, new electrolyzer technologies such as solid oxide electrolyzers (SOECs) and proton exchange membrane electrolyzers (PEMs) have shown great potential in increasing current density and reducing energy consumption. PEM water electrolysis has entered the market with a more compact system design, lower ohmic losses, a larger load range and faster system response. PEM relies on traditional ionomer perfluorosulfonic acid resin (Nafion) to conduct protons and bind catalysts. However, it is difficult for catalysts to maintain good stability under such acidic conditions, which restricts the choice of catalysts. In order to achieve large-scale application of PEM water electrolysis, non-precious metal catalysts are needed to replace precious metal catalysts. Past efforts have focused on the development of advanced catalysts, ignoring the role of ionomers on the catalytic interface. Therefore, optimizing ionomers may be another way to improve the overall stability of PEM.
[0004] The anode reaction of PEM water electrolysis is the oxygen evolution reaction (OER), and the reaction steps involve the breaking of hydrogen-oxygen bonds and are also related to the transfer of protons. Excessive protons cause local acidity to increase, which can easily cause the catalyst structure to collapse. At the same time, sulfonate groups may coordinate with the catalyst surface at high potentials, further reducing stability. Therefore, strategies such as optimizing the hydrogen-bonded water network, increasing the hydrophilic channels, and inhibiting sulfonate coordination can help improve the stability of water decomposition, especially when applied to non-precious metal catalysts.
[0005] Unfortunately, most of the current Nafion modifications are based on the application of electrolyte membranes, and membranes have extremely high requirements for mechanical strength, while ionomers do not. Some dopants, such as silicon oxide nanoparticles, easily block catalytic sites and are not suitable for ionomer modification. Small molecules are easily lost during the reaction, making the stability worse. In summary, choosing a small molecule that has a strong interaction with Nafion is an excellent strategy. Here, CF3 (CF2) is chosen. nThe CH2OH series, with a hydrophobic carbon fluorine structure and a hydrophilic hydroxyl group at the tail end, can play a role similar to that of a surfactant, building a bridge between the hydrophilic and hydrophobic regions of Nafion through self-assembly, thereby optimizing the water channel. The hydroxyl group may also coordinate with the sulfonic acid group, improving the hydrogen bond water network while inhibiting the coordination of the sulfonic acid group with the catalyst, thereby achieving multifunctional optimization of PEM performance. Summary of the invention
[0006] The object of the present invention is to provide a PEM water electrolysis model electrode based on modified Nafion ionomer and a preparation method thereof, so as to improve the stability of the catalyst in the practical application of PEM water electrolysis.
[0007] The present invention first provides a modified Nafion ionomer obtained by doping a commercial Nafion ionomer (or solid membrane), denoted as FOH. n -Nafion ionomer, the structural formula of which is shown in the following formula (I):
[0008]
[0009] Wherein, for Nafion membrane with an equivalent weight (EW) of 1100 g / eq, x is 6;
[0010] Among them, the dopant is CF3(CF2) n CH2OH, n is 2-10.
[0011] In the present invention, the mass ratio of the dopant to the Nafion ionomer (or solid membrane) is 0.2-4.0; preferably, the doping mass ratio is 0.5-2.
[0012] The present invention also provides FOH n -The preparation method of Nafion ionomer, that is, the Nafion modification method, comprises the following specific steps:
[0013] (1) According to the doping mass ratio, weigh the doping molecules CF3 (CF2) respectively. n CH2OH and Nafion ionomer solution or solid membrane;
[0014] (2) Modification of ionomer solution: CF3(CF2) n CH2OH is dissolved in the Nafion ionomer solution, placed in a sealed container and heated and stirred to obtain a mixed solution; for the modification of the solid membrane: the solid membrane is directly immersed in the corresponding amount of doping molecules for 0.5-6 hours, and then dried at 40-80°C.
[0015] Further:
[0016] The doping mass ratio is 0.2-4.0; preferably the doping mass ratio is 0.5-2;
[0017] The mass fraction of the Nafion ionomer solution used is 5-20%; the preferred mass fraction of the solution is 5-10%;
[0018] The heating temperature is 40-80°C; preferably the heating temperature is 60-70°C;
[0019] The heating time is 0.5-6 hours; preferably the heating time is 2-4 hours;
[0020] The present invention provides a method for preparing a PEM water electrolysis model electrode based on a modified Nafion ionomer, and the specific steps are as follows:
[0021] (1) According to the mass ratio of Nafion and catalyst, weigh FOH n -Nafion and catalyst are added into ethanol or isopropanol and dispersed evenly by ultrasonication to obtain catalyst slurry;
[0022] (2) placing the Nafion membrane on a vacuum adsorption hot table, and uniformly coating the prepared catalyst slurry on the Nafion membrane by ultrasonic spraying or doctor blade coating;
[0023] (3) First perform hot pressing and fixation, then perform cold pressing and plasticization to obtain a PEM electrolysis water model electrode.
[0024] In step (1):
[0025] The catalyst can be cobalt tetraoxide type, manganese dioxide type, ruthenium oxide type catalyst, and the loading is controlled at 1.5-3 mg / cm 2 ;
[0026] The mass ratio of the Nafion to the catalyst is 0.2-0.4.
[0027] The mass fraction of the ethanol or isopropanol is 70-99%, and the volume is 1-5 ml; the oscillation ultrasonic time is 5-60 min.
[0028] The Nafion membrane models may be Nafion 212, Nafion 211, Nafion 117 and Nafion 115.
[0029] In step (3), the hot pressing pressure is 1-4 MPa, the temperature is 60-100° C., and the time is 3-10 min. The cold pressing is at room temperature, and the other parameters are the same as those of the hot pressing.
[0030] The present invention also provides a method for testing the performance of the ionomer membrane electrode, the specific steps of which are as follows:
[0031] (1) Prepare cathode catalyst slurry. Specifically, 20-60% Pt / C is used, and the mass ratio of Nafion to catalyst is 0.2-0.4. n -Nafion and catalyst are ultrasonically mixed with appropriate amount of ethanol or isopropanol to form catalyst slurry, and then sprayed on carbon paper or the cathode side of the membrane electrode, with the loading controlled at 0.2-0.4 mg Pt / cm 2 ;
[0032] (2) Platinum-plated titanium felt is selected as the gas diffusion layer on the anode side of the membrane electrode, and titanium plates on both sides are used as current collectors to build a PEM electrolyzer; the water inflow rate is 30-80 ml / min, and the temperature is 60-90 °C;
[0033] (3) First, at a current density of 20 mA / cm 2 Activate for 2-10 hours, then increase the current density stepwise to 1000mA / cm 2 .
[0034] The technical features and functional advantages of the present invention mainly include:
[0035] The modified FOH of the present invention n -Nafion ionomers have higher electrolytic cell stability than commercial Nafion ionomers. The modification method of the present invention is simple and applicable to a variety of syntheses. The modified molecules are easily available and easy to mass produce at low cost. The modified Nafion ionomer can be used with a variety of PEMWE anode catalysts. Without changing the catalyst, the stability can be significantly improved by simply optimizing the reaction interface. It has a certain universality, especially for cobalt tetroxide catalysts. When the PEMWE current density is 1A cm -2 The voltage was only 1.84V, while the voltage was 1.87V when using commercial Nafion ionomer at the same current density, and it became inactivated after 4 hours of operation. The excellent performance of PEMWE is due to the incorporation of amphiphilic molecules. The carbon fluorine chain is well compatible with the hydrophobic main chain of Nafion, while the hydroxyl group can interact with the sulfonic acid group to optimize the hydrogen bond water network and introduce water molecules into the hydrophobic side, expanding the water transfer space. Combining all the effects, the modified Nafion improves the stability of non-precious metal catalysts, which is expected to promote the popularization and application of PEMWE. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The corresponding values of Example 1 (FOH2-Nafion) and Comparative Example 1 (Nafion) of the present invention are 1 H NMR spectrum.
[0037] Figure 2This is a high-resolution transmission electron microscopy (HRTEM) image of Example 1 (FOH2-Nafion) of the present invention.
[0038] Figure 3 This is a high-resolution transmission electron microscopy (HRTEM) image of Comparative Example 1 (Nafion) of the present invention.
[0039] Figure 4 The graph of proton conductivity variation with temperature of Example 7 of the present invention and Comparative Example 2 is shown.
[0040] Figure 5 The AC impedance spectra of Example 1 (FOH2-Nafion) of the present invention and Comparative Example 1 (Nafion) are shown.
[0041] Figure 6 PEM tests of Example 1 (FOH2-Nafion), Example 4 (FOH4-Nafion) and Comparative Example 1 (Nafion) of the present invention. DETAILED DESCRIPTION
[0042] The present invention is further described below by way of embodiments in conjunction with the accompanying drawings.
[0043] Embodiment 1:
[0044] CF3CF2CF2CH2OH and 5% Nafion solution were weighed at a doping mass ratio of 0.5. CF3CF2CF2CH2OH was added to the Nafion solution, placed in a sealed container, heated and stirred for 1 hour at a heating temperature of 60° C. to obtain a modified ionomer solution.
[0045] Embodiment 2:
[0046] According to the doping mass ratio of 1.0, CF3CF2CF2CH2OH and 10% Nafion solution were weighed respectively. CF3CF2CF2CH2OH was added to the Nafion solution, placed in a sealed container, heated and stirred for 3 hours at a heating temperature of 60° C. to obtain a modified ionomer solution.
[0047] Embodiment 3:
[0048] According to the doping mass ratio of 3.0, CF3CF2CF2CH2OH and 5% Nafion solution were weighed respectively. CF3CF2CF2CH2OH was added to the Nafion solution, placed in a sealed container, heated and stirred for 2 hours at a heating temperature of 80° C. to obtain a modified ionomer solution.
[0049] Embodiment 4:
[0050] According to the doping mass ratio of 0.5, CF3CF2CF2CF2CF2CH2OH and 5% Nafion solution were weighed respectively. CF3CF2CF2CF2CF2CH2OH was added to the Nafion solution, placed in a sealed container, heated and stirred for 3 hours at a heating temperature of 60°C to obtain a modified ionomer solution.
[0051] Embodiment 5:
[0052] According to the doping mass ratio of 0.5, CF3CF2CF2CF2CF2CF2CF2CH2OH and 5% Nafion solution were weighed respectively. CF3CF2CF2CF2CF2CF2CH2OH was added to the Nafion solution, placed in a sealed container, heated and stirred for 1 hour at a heating temperature of 40°C to obtain a modified ionomer solution.
[0053] Embodiment 6:
[0054] According to the doping mass ratio of 0.5, CF3CF2CF2CF2CF2CF2CF2CF2CF2CH2OH and 5% Nafion solution were weighed respectively. CF3CF2CF2CF2CF2CF2CH2OH was added to the Nafion solution, placed in a sealed container, heated and stirred for 1 hour at a heating temperature of 40°C to obtain a modified ionomer solution.
[0055] Embodiment 7:
[0056] According to the doping mass ratio of 1.0, the doping molecules CF3CF2CF2CH2OH and the Nafion membrane were weighed respectively. The membrane was immersed in the corresponding amount of doping molecule solvent for 1 hour, and then dried at 40°C to obtain a modified membrane.
[0057] Embodiment 8:
[0058] According to the doping mass ratio of 1.0, the doping molecules CF3CF2CF2CF2CF2CH2OH and the Nafion membrane were weighed respectively. The membrane was immersed in the corresponding amount of doping molecule solvent for 1 hour, and then dried at 60°C to obtain a modified membrane.
[0059] Comparative Example 1:
[0060] Weigh 5% Nafion solution, place the Nafion solution in a sealed container, heat and stir for 1 hour, and the heating temperature is 60°C.
[0061] Comparative Example 2:
[0062] According to the doping mass ratio of 1.0, ethanol and Nafion membrane were weighed respectively, the Nafion membrane was immersed in ethanol for 1 hour, and then dried at 60° C. to obtain a modified membrane.
[0063] Structural characterization of the modified ionomers of Examples 1-6 and Comparative Example 1.
[0064] use 1 H NMR was used to characterize Example 1 and Comparative Example 1. Figure 1 The original hydrogen peak of the sulfonic acid group and the CF3CF2CF2CH2OH hydroxyl hydrogen peak disappeared and merged into a broad peak in the middle position, indicating that the hydroxyl group reacted with the sulfonic acid group, as shown in its structural formula.
[0065] The microscopic morphology of Example 1 and Comparative Example 1 was obtained by HRTEM. Figure 2 , Figure 3 .contrast Figure 2 and Figure 3 , it can be found that Nafion has dark circular areas, which are clusters of sulfonate groups. n -The circular areas in Nafion are larger and lighter in color, indicating that the sulfonate clusters are dispersed, the hydrophilic areas are enlarged, and they are intertwined with the hydrophobic areas.
[0066] The structural characterization results of Examples 2-6 are similar to those of Example 1 and are not repeated here.
[0067] Preparation of membrane electrode: FOH was weighed according to the mass ratio of ionomer to cobalt tetroxide catalyst of 0.3. n -Nafion and catalyst are added to ethanol or isopropanol and dispersed evenly by ultrasonication to obtain catalyst slurry. The Nafion membrane is placed on a vacuum adsorption hot table, and the prepared catalyst slurry is evenly coated on the Nafion membrane by ultrasonic spraying or scraping, and the loading is controlled at 1.5-3 mg / cm 2 The membrane electrode was obtained by hot pressing at 80°C and 1MPa for 5 minutes, and then cold pressing for plasticity. The membrane electrode was obtained by cold pressing at room temperature.
[0068] Proton conductivity test of the modified membranes of Examples 7-8 and Comparative Example 2:
[0069] Since it is impossible to directly measure the proton conductivity of the ionomer, the modified membrane was selected as the object of qualitative research. The membrane to be tested was first immersed in ultrapure water for 10 hours. Then, the two-electrode four-probe method was used to test the membrane in pure water for AC impedance spectroscopy. The temperature ranged from 18 to 50°C, and each temperature was stabilized for 15 minutes before testing. The frequency ranged from 10 6 to 1, with an amplitude of 5mV.
[0070] The test results of Example 8 are similar to those of Example 7. The proton conductivity is significantly improved compared with that of Comparative Example 2, showing good proton transfer ability. Figure 4 .
[0071] For membrane electrode testing, cathode catalyst slurry was prepared, 40% Pt / C was selected, Nafion ionomer with a mass ratio of 0.3 was added, and the catalyst slurry was ultrasonically prepared with an appropriate amount of ethanol or isopropanol, and then sprayed on carbon paper or the cathode side of the membrane electrode, and the loading was controlled at 0.2-0.4 mg. Pt / cm 2 . Platinum-plated titanium felt was selected as the gas diffusion layer on the anode side, and titanium plates on both sides were used as current collectors to build a PEM electrolyzer. The water inlet rate was 30-80ml / min and the temperature was 60-90℃. First, the PEM was allowed to flow at a current density of 20mA / cm 2 Activate for 2-10 hours, then increase the current density stepwise to 1000mA / cm 2 For the AC impedance spectrum test in PEM, the voltage is 1.6V and the frequency range is 10 5 to 0.01, with an amplitude of 10mV.
[0072] In the PEMWE, AC impedance test, the results of Examples 2-6 are similar to those of Example 1. The charge transfer resistance at a voltage of 1.6 V is less than that of Comparative Example 1. Figure 5 In the PEMWE stability test, the results of Examples 2-3 are similar to those of Example 1. The results of Examples 5-6 are similar to those of Example 4. Figure 6 Example 1 in PEMWE 1A / cm 2 It can work continuously for 40 hours under working conditions, and its stability is better than that of comparative example 1, showing outstanding water electrolysis performance.
[0073] In summary, the present invention demonstrates a doping modification method for Nafion ionomer and Nafion membrane and a membrane electrode preparation and testing method. n CH2OH regulates the distribution of the hydrophilic and hydrophobic phases of Nafion, making the cobalt tetroxide catalyst 1A / cm 2 Under working conditions, it can work continuously for 40 hours, showing good stability. The ionomer gives non-precious metal catalysts higher activity and has certain industrial application prospects. It is expected to replace precious metal catalysts, reduce production costs, and promote the popularization of PEM water electrolysis.
[0074] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A modified Nafion ionomer, characterized in that it is obtained by doping and modifying a Nafion ionomer or a solid membrane, denoted as FOH n -Nafion ionomer, the structural formula of which is shown in the following formula (I): Wherein, for Nafion membrane with an equivalent weight (EW) of 1100 g / eq, x is 6; in, The dopant is CF3(CF2) n CH2OH, n is 2-10; The mass ratio of the dopant to the Nafion ionomer or solid membrane is 0.2-4.
0.
2. The method for preparing the modified Nafion ionomer according to claim 1, characterized in that: The specific steps are: (1) According to the doping mass ratio, weigh the doping molecules CF3 (CF2) respectively. n CH2OH and Nafion ionomer solution or solid membrane; (2) Modification of ionomer solution: CF3(CF2) n CH2OH is dissolved in the Nafion ionomer solution, placed in a sealed container and heated and stirred to obtain a mixed solution; for the modification of the solid membrane: the solid membrane is directly immersed in the corresponding amount of doping molecules for 0.5-6 hours, and then dried at 40-80°C.
3. The preparation method according to claim 2, characterized in that: The doping mass ratio is 0.2-4.0; The mass fraction of the Nafion ionomer solution used is 5-20%; The heating temperature is 40-80°C; The heating time is 0.5-6 hours.
4. A method for preparing a PEM water electrolysis model electrode based on modified Nafion ionomer, characterized in that: The specific steps are as follows: (I) Preparation of modified Nafion ionomer, the specific steps are: (1) According to the doping mass ratio, weigh the doping molecules CF3 (CF2) respectively. n CH2OH and Nafion ionomer solution or solid membrane; (2) Modification of ionomer solution: CF3(CF2) n CH2OH is dissolved in the Nafion ionomer solution, placed in a sealed container and heated and stirred to obtain a mixed solution; for the modification of the solid membrane: the solid membrane is directly immersed in the corresponding amount of doping molecules for 0.5-6 hours, and then dried at 40-80°C; the modified Nafion ionomer is recorded as FOH n -Nafion; (II) Preparation of PEM water electrolysis model electrode, (1) According to the mass ratio of Nafion and catalyst, weigh FOH n -Nafion and catalyst are added into ethanol or isopropanol and dispersed evenly by ultrasonication to obtain catalyst slurry; (2) placing the Nafion membrane on a vacuum adsorption hot table, and uniformly coating the prepared catalyst slurry on the Nafion membrane by ultrasonic spraying or doctor blade coating; (3) First perform hot pressing and fixation, then perform cold pressing and plasticization to obtain a PEM electrolysis water model electrode.
5. The preparation method according to claim 4, characterized in that: In step (1): The doping mass ratio is 0.2-4.0; The mass fraction of the Nafion ionomer solution used is 5-20%; The heating temperature is 40-80°C; The heating time is 0.5-6 hours.
6. The preparation method according to claim 5, characterized in that: In step (2): The catalyst is cobalt tetraoxide type, manganese dioxide type, ruthenium oxide type catalyst, and the loading is 1.5-3 mg / cm 2 ; The mass ratio of Nafion to catalyst is 0.2-0.4; The ethanol or isopropanol has a mass fraction of 70-99% and a volume of 1-5 ml; the oscillation ultrasonic time is 5-60 min; The hot pressing pressure is 1-4MPa, the temperature is 60-100°C, and the time is 3-10min; the cold pressing is at room temperature, and the other parameters are the same as those of the hot pressing.
7. A PEM water electrolysis model electrode based on modified Nafion ionomer obtained by the preparation method according to any one of claims 4 to 6.
8. A method for testing the performance of a PEM water electrolysis model electrode as claimed in claim 7, characterized in that: The specific steps are as follows: (1) Prepare cathode catalyst slurry; specifically, use 20-60% Pt / C, and weigh FOH, according to the mass ratio of Nafion to catalyst of 0.2-0.
4. n -Nafion and catalyst are ultrasonically mixed with appropriate amount of ethanol or isopropanol to form catalyst slurry, and then sprayed on carbon paper or the cathode side of the membrane electrode, with the loading controlled at 0.2-0.4 mg Pt / cm 2 ; (2) Platinum-plated titanium felt is selected as the gas diffusion layer on the anode side of the membrane electrode, and titanium plates on both sides are used as current collectors to build a PEM electrolyzer; the water inflow rate is 30-80 ml / min, and the temperature is 60-90 °C; (3) First, at a current density of 20 mA / cm 2 Activate for 2-10 hours, then increase the current density stepwise to 1000mA / cm 2 .
Citation Information
Patent Citations
Preparation method of catalyst layer slurry of proton exchange membrane fuel cell and membrane electrode
CN113745534A